Dielectric particle-based strategy to design a new self-bending subwavelength structured light beams; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Minin I. V. Igor Vladilenovich (2021, 2021)
Title screen